Bioavailability, antioxidant and non toxic properties of a radioprotective formulation prepared from isolated compounds of Podophyllum hexandrum: a study in mouse model - Dutta, A.; Verma, S.; Sankhwar, S.; Flora, S. J. S.; Gupta, M. L. (Cellular and Molecular Biology, 2012)
The current study was aimed to determine the stability, serum protein binding ability, biodistribution, antioxidant potential and tissue toxicity status of a novel radioprotective formulation (G-002M) from Podophyllum hexandrum. G-002M is the combination of a flavonoid, a lignan and its glucoside isolated from P. hexandrum rhizome that exhibit high radioprotective potential. Stability of G-002M tagged with 99mTc was observed in vitro and with mice serum till 24 hr of incubation. The formulation was investigated for its antioxidant status and its bioavailability and toxicity in different organs of mice. Biodistribution study of 99mTc-G-002M revealed its uptake by all the vital organs of mice. Higher absorbed dose was observed in lungs, liver, jejunum and kidney. Maximum retention of G-002M in kidney revealed that G-002M was excreted predominantly through renal route. G-002M was also observed to have high free radical scavenging and total reducing properties. Histopathological observations showed no significant alterations in tissue morphology of lungs, liver, jejunum and kidney by G-002M administration. The data conclusively demonstrate that high stability, multi organ availability, longer retention and non-toxic behavior of G-002M might help in exhibiting strong protective potential against lethal radiation.